IMMUNOLOGICAL AND PSYCHOPHYSIOLOGICAL HETEROGENEITY AMONG PATIENTS WITH BRONCHIAL ASTHMA - A. V. Smyk (SPb RAACI, 2014)
Abstract. Bronchial asthma is a classic psychosomatic disease by immunopathological origin. In present investigation, we studied influence of body-oriented psychotherapeutic methods directed towards clinico-immunological parameters and special psychological features of the patients with bronchial asthma, i.e., decrease in alexithymia, as an important pathogenetic factor of bronchial asthma, and improvement in motor coordination and interhemispheric interactions in motor sphere. We investigated 38 patients (18 men and 20 women), while discriminating those patients who underwent a course of body-oriented psychotherapy, and a group of comparison, who did not undergo similar therapy. When observing conventional standards of randomization according to sex, age, clinical variants, and disease severity, some heterogeneity of these groups was revealed. In general, the people with active life attitude, being ready to work with a psychologist, possessed special features both in psychological and immunological spheres.